Cultural constructions of illness : the client and practitioner perspectives of traditional Chinese medicine. Perth Western Australia - Greene, Patricia Ann (Curtin University, 2011)
An increased use of Complementary and alternate health care practices (CAM) and under which TCM is found assumed, is found in overseas countries and has become increasingly popular among Australian consumer. There has been a considerably increase in the consumer use of TCM over the past decade, but little is understood on the practice of the clinical encounter in TCM explained from the context within a clinic in western society.Investigation was made on how social and cultural processes have shaped people’s acceptance of TCM as a form of complementary health. Drawing from an ethnographic focus, the study explores the practice of TCM in several clinic settings in Perth. Attention is paid to the ways in which notions of health and illness are constructed by clients and practitioners. This study examined the interactions found in the process of ‘Kanbing’ from a TCM practice in Perth, Western Australia in order to understand how health practices are shaped by cultural and social processes. From an anthropological perspective, the ethnography of this study was guided an extended contact with the everyday clinical context of TCM, facilitated through participant observation, interviews with clients and practitioners and case study analysis. Interviews revealed perspectives from clients of non-Asian backgrounds to record the lived experiences of the encounters between the practitioner and client of TCM in the clinic. Participant observation took place over a two year period from February 2002 to March 2003 with further follow up work in the field conducted at intervals throughout 2004 and 2006 to gain additional data.The client centred interrelationships between practitioners of TCM, clients, and their perceptions, formed part of the interpretative process that informed the understanding of the cultural context from how an illness is described and explained through the process of Kanbing. My research was drawn from the reality of the encounter within the clinical context through participant observation within two western clinics of TCM. Thus the study makes a contribution to anthropology on the understanding of the structure and meaning found within the practice of traditional Chinese medicine in Australia.